Peer Education for STI Prevention in the LGBTQ Community of Palu: Insights, Barriers, and Impact - Yani, Ahmad (Journal of Health Literacy and Qualitative Research, 2022)
The LGBTQ community faces significant barriers in accessing inclusive healthcare services, particularly regarding sexually transmitted infection (STI) prevention. Peer education has emerged as an effective strategy for improving STI awareness and promoting safer health behaviors within this community. This study employs a qualitative case study approach, conducting in-depth semi-structured interviews with LGBTQ individuals in Palu, Indonesia, to assess the impact of peer education on STI prevention. Findings indicate that peer education effectively enhances STI awareness and encourages preventive behaviors by leveraging community trust and shared lived experiences. Participants reported increased knowledge, behavioral shifts toward safer practices, and greater comfort in discussing sexual health issues with peer educators. Despite these benefits, the study identifies structural barriers, including financial constraints, healthcare discrimination, and limited government support, as significant obstacles to program effectiveness. Addressing these challenges requires enhanced policy support, institutionalized LGBTQ-inclusive healthcare training, and expanded funding for community-based interventions. This study contributes to public health research by emphasizing the importance of peer-led education in STI prevention strategies and advocating for multi-sectoral collaboration to ensure sustainable, inclusive healthcare services for LGBTQ individuals.